(untitled) (Journal of Geography and Environmental Management, 2021)
The article discusses the qualitative state of agricultural land in the Turkestan region. Using statistical data in recent years, the dynamics of changes in the areas of arable land is shown, negative factors affecting the quality of agricultural land are identified.. The main factor in the degradation of agricultural land in the region is erosion. The article identifies priority areas for the effective use of agricultural land, taking into account regional peculiarities of the region and outlines the issues of improving their effective use.The article discusses the three main structures for the sustainable development of agriculture and the agro-industrial complex, which are important in the rational management of agriculture and land resources. Analyzed the European version of the development of agricultural land and agriculture in Europe under the program of the European Union ERA-NET. The experience of developed countries such as Australia, Canada, Russia is considered and recommendations are given on improving the quality of agricultural land in the Turkestan region.